High Levels of Cerebrospinal Fluid Kappa Free Light Chains Relate to IgM Intrathecal Synthesis and Might Have Prognostic Implications in Relapsing Multiple Sclerosis - Castillo-Villalba, Jéssica; Gil-Perotín, Sara; Gasque-Rubio, Raquel; Cubas-Nuñez, Laura; Carratalà-Boscà, Sara; Alcalá, Carmen; Quintanilla-Bordás, Carlos; Pérez-Miralles, Francisco; Ferrer, Cristina; Cañada Martínez, Antonio; Tortosa, Jordi; Solís-Tarazona, Luís; et al. (Frontiers in Immunology, 2022)
Cerebrospinal kappa free light chain (KFLC)-index is a marker of intrathecal immunoglobulin synthesis that aids in the diagnosis of multiple sclerosis (MS). However, little evidence exists on its prognostic role. Our aim is to analyze the relationship between KFLC-index and other MS biomarkers and to explore its prognostic role. This is a monocentric observational study in a cohort of 52 people with relapsing MS (pwRMS) performed on prospectively acquired clinical data and with retrospective evaluation of biomarkers. We measured KFLC-index, immunoglobulin intrathecal synthesis, cerebrospinal fluid (CSF) chitinase 3-like 1 (CHI3L1), and neurofilament light protein (NFL) and reviewed MRI to detect leptomeningeal contrast enhancement (LMCE). We compared time to Expanded Disability Status Scale (EDSS) 3 and to initiation of high-efficacy disease-modifying therapies (heDMTs) by multivariate Cox regression analysis. Median KFLC-index correlated with IgG/IgM indexes (p < 0.0001/p < 0.05) and IgG-oligoclonal bands (OCGBs) (p < 0.001). Patients with IgM-oligoclonal bands (OCMBs) had a higher KFLC-index (p = 0.049). KFLC-index was higher in patients with LMCE (p = 0.008) and correlated with CHI3L1 (p = 0.007), but disease activity had no effect on its value. Bivariate and multivariate analyses confirmed KFLC-index > 58 as an independent risk factor for reaching an EDSS of 3 (hazard ratio (HR) = 12.4; 95% CI = 1.1–147; p = 0.047) and for the need of treatment with heDMTs (HR = 3.0; 95% CI = 1.2–7.1; p = 0.0013). To conclude, our data suggest a potential prognostic role of the KFLC-index during the MS course.